THE ROLE OF UNITED NATIONS IN PTOMOTING HUMAN RIGHT IN TURKMENISTAN DURING SAPARMURAT NIYAZOV ERA - M. Arsy Ash Shiddiqi (Universitas Muhammadiyah Yogyakarta, 2011)
THE ROLE OF UNITED NATIONS IN PTOMOTING HUMAN RIGHT IN TURKMENISTAN DURING SAPARMURAT NIYAZOV ERA